A framework of enhanced authentication for PDF textual documents using Zigzag-LSB embedding algorithm - Nur Alya Afikah, Usop (2024)
The security level for documents is necessary since a lot of formal procedures and processes nowadays need digital documents as proof or process verification, such as internet banking receipts, official letters of appointment, academic transcripts and certificates, scanned documents, and commercial documents for online marketing. The phenomenon of widespread usage of digital documents in emails, social networking sites, e-commerce websites, and many government-linked websites is a trend for reaching the audience, saving processing time and paper resources, as well as cutting the cost of postage. The rapid advancement of information technology in digital multimedia means that the original content of documents can be easily manipulated, edited, or tampered with by others. Hence, a digital watermarking procedure is needed to detect any changes in of the original information in document becomes necessary. A framework of enhanced authentication for PDF textual documents using Zigzag-lsb embedding algorithm is proposed in order to apply a new technique of watermarking scheme which can be used in general size of document, to study the current numbering of watermarking system to secure the authentication of digital documents, and evaluate the watermarking scheme for digital documents in terms of accuracy rate, and analyse the performance. Least significant bits (LSB) were used by the techniques to encrypt authentication data. By dispersing the numbered original data as far away from the original locations as feasible, the strategies made use of specific numbering systems. Similar processes are used in the generation and embedding phases of a watermark. The effectiveness of the algorithm has been established since it uses an image-based approach after conversion between document and images with a numbering pattern that is fragile to deletion, replacement, insertion, combine, and copy attack. As a conclusion, the new numbering pattern have demonstrated to be more competent compared to the existing numbering pattern in watermarking since the results have shown the best performance in terms of accuracy rate.